Study on Micromachining of Polycrystalline Diamond by UV Nanosecond Laser. Issue 1 (2nd September 2021) - Fang, Xuyang; Cui, Jianlei; Fan, Zhengjie; Sun, Zheng; Mei, Xuesong
Abstract: A single-wire cutting experiment on the polycrystalline diamond by UV nanosecond laser was carried out. The result was characterized and analyzed by the scanning electron microscope and XPS energy spectrum analysis. It found that the width and depth of grooves continue to increase with the increasing of laser power, scanning times, and the decreasing of scanning speed. A finer groove with a narrower width and deeper depth can be obtained by adjusting the focus point on the surface of the PCD material. XPS spectrum of C1s indicated that sp 3 structure converts to the sp 2 graphite phase and removed by photochemical mechanism when the UV nanosecond laser irradiates the PCD. Moreover, the cutting result suggests that UV nanosecond laser can achieve finer processing of PCD material.